2011
DOI: 10.1007/s11664-011-1764-0
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Better Understanding of the Effect of Cu Electroplating Process Parameters on Cu3Sn Voiding

Abstract: Kirkendall voiding'' in the interfacial Cu 3 Sn intermetallic compound is often observed in solder joints made between Sn-containing alloys and Cu interconnect pads, during extended thermal aging or electromigration testing. It is commonly believed that voids arise from the Kirkendall effect, i.e., the imbalance of diffusion fluxes of Cu and Sn atoms in Cu 3 Sn. However, recent studies have demonstrated that the propensity for voiding is greatly affected by the amount of organic impurities incorporated during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 37 publications
1
25
1
1
Order By: Relevance
“…Yin et al 10,11,21 also found a similar result. However, the void quantity was much higher in the present work.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Yin et al 10,11,21 also found a similar result. However, the void quantity was much higher in the present work.…”
Section: Resultsmentioning
confidence: 52%
“…However, the void quantity was much higher in the present work. Yin et al 11 found that voids were formed only at the Cu/Cu 3 Sn interface and aggregated to form a continuous gap along the interface upon annealing. In the present work, numerous voids were formed not only at the interface but also within the IMC layers, forming a complicated alternating layered structure as seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult from this work to confidently conclude that substrate orientation plays a role in void formation, rather one would expect the changes in the current density would play a much larger role in void formation. Yin et al 87 studied texturing of various typical suppressor-accelerator additive systems. A texture coefficient was used to measure the amount of texturing occurring in the samples with respect to the voiding propensity.…”
Section: Changes In the Microstructurementioning
confidence: 99%
“…In case of Cu-solder reaction, many studies have reported that Cu plating conditions such as additives are related to microvoid formation at the CuCu 3 Sn interface, affecting the final solder joint reliability. [13][14][15][16][17] In case of Ni-solder reaction, it is reported that the Ni-P plating bath life affects the brittle fracture behavior of Sn-Ag-Cu solder joints. 18 However, few studies have investigated the effect of Ni-P plating conditions on solder joint properties.…”
Section: Introductionmentioning
confidence: 99%